Seed Bank Estimation and Regeneration Studies of Madhuca neriifolia (Moon) H.J. Lam., from Western Ghats of Karnataka - Prasanna Kumar, C. N.; Somashekar, R. K.; Nagaraja, B. C.; Shivaprasad, D. (Indian Forester, 2017)
Studies on the seed dispersal, regeneration by both in-situ and ex-situ are crucial for the management of genetic diversity of threatened species. The seed bank estimation was assessed on an endangered species Madhuca neriifolia from three different locations of Western Ghats using two factorial completely randomized design. The seeds are dispersed by anemochory, hydrochory and mammalochory. The natural seed bank estimation revealed the seed densities among the forest ranges and distances are significant. The in-situ regeneration among the forest ranges and the distances were insignificant. The mean percentage of ex-situ regeneration was remained insignificant among the forest ranges and the seeds collected from the different distances. The high mean percentageof ex-situ regeneration suggests it as a best suitable method to conserve this endangered species.